Cidade, caminhos e croquis: relações entre a desnaturalização do rio da Costa e a evolução urbana de Vila Velha-ES - Martins, Bruno Giorgio D Alessandri (2022)
The consolidation of urban centers is often linked to modifications of the original sites in which they are located, leading to interventions in the landscape and in natural elements. It is believed that these actions reflect changes in ecosystems and in people's contact and belonging with urban waters, changing their subjective values and quality of life. In this sense, the relationship between rivers and cities can become conflictive when, in the name of flood control and urban expansion, water courses and their floodplain areas are suppressed, fragmented, degraded and channeled. The Costa River, in Vila Velha-ES, is an example of these cases and the object of this work, which proposes to investigate the denaturalization of the river and the evolution of the urban form, seeking to understand how these processes were associated and influenced the bonds of people with the now Costa channel. To reach these interfaces, the methodology mixes three types of views on the object: the visions of the urban planner, the walker and the living, which involve the theoretical foundation and permeate between the procedures. The application of the methods begins with the historical documentary research of the city's growth associated with the denaturalization of the Costa River, based on books, academic publications, photographs, maps and illustrations, generating a periodization in four stages of interventions. Then, these periods were related to studies by Macedo (1999), justifying aspects of coastal urbanization, and the evolution of urban form, according to the methodology of Costa and Netto (2015). From these studies, it is understood that the transformation of the river into a channel on the Coast is linked to a model of formation of Brazilian cities that generalizes the territory and, therefore, the object has changed due to occupation and has moved away from its natural characteristics. The scale of analysis is later approximated by dividing the channel into sectors, according to Mendonça (2002) method, and with the development of walks and sketches that show the uses, problems and particularities of its banks. In addition, the urban legislation that regulates the occupation of the surroundings of the object was raised, showing that apparently there is no interest in valuing it as a water body and incorporating it into the urban fabric. Finally, the research presents subjective and qualitative aspects resulting from walks and contact with residents and passers-by, translated into reports and sketches that show contrasts in the relationship between the canal and the city. The research reveals that the Costa channel holds the past of a locally important river, but considered as a ditch and invisible in the urban form, as a result of the dense occupation of the coastal plain under fluvial, pluvial and maritime influence. Based on the hypothesis that the object can be re-signified as a structuring and potentially aggregating urban and ecological element in the landscape of Vila Velha, it is concluded that future interventions in the canal need, in addition to preventing flooding, to seek ways to incorporate urban waters into the city.